1997
DOI: 10.1037/0022-3514.72.5.1132
|View full text |Cite
|
Sign up to set email alerts
|

Terror management and cognitive-experiential self-theory: Evidence that terror management occurs in the experiential system.

Abstract: The authors hypothesized, on the basis of terror management theory and cognitive-experiential self-theory, that participants in an experiential mode of thinking would respond to mortality salience with increased worldview defense and increased accessibility of death-related thoughts, whereas participants in a rational mode would not. Results from 3 studies provided convergent evidence that when participants were in an experiential mode, mortality salience produced the typical worldview defense effect, but when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
115
2
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 154 publications
(122 citation statements)
references
References 51 publications
4
115
2
1
Order By: Relevance
“…Obviously, the approaches used in this study to activate rational and experiential processing (using math problems and creative drawing exercises) would not be utilized in the courtroom. However, other research on the effects of CEST has shown that processing mode can be successfully manipulated by giving participants direct instructions to think rationally and analytically, or to go with their ''gut-level'' feelings (Lieberman, 2002;Lieberman & Greenberg, manuscript submitted for publication; Simon et al, 1996). Thus, it should be possible to develop effective procedural instructions in this regard.…”
Section: Trial Procedures Implicationsmentioning
confidence: 99%
“…Obviously, the approaches used in this study to activate rational and experiential processing (using math problems and creative drawing exercises) would not be utilized in the courtroom. However, other research on the effects of CEST has shown that processing mode can be successfully manipulated by giving participants direct instructions to think rationally and analytically, or to go with their ''gut-level'' feelings (Lieberman, 2002;Lieberman & Greenberg, manuscript submitted for publication; Simon et al, 1996). Thus, it should be possible to develop effective procedural instructions in this regard.…”
Section: Trial Procedures Implicationsmentioning
confidence: 99%
“…Then, in Study 3, we determined if reminders of 9/11 function like MS primes in increasing support for President Bush. STUDY 2 Support for the dual process model has been obtained from studies showing that MS inductions that completely by-pass the conscious consideration of death can influence symbolic defenses (Arndt, Greenberg, Pyszczynski, & Solomon, 1997). More specifically, Arndt et al demonstrated that presenting death-related words beneath conscious awareness led to an immediate increase in death-thought accessibility relative to neutral or negative control words.…”
Section: /11 and Support For Bushmentioning
confidence: 99%
“…The more emotionally charged a situation is, the more the person's thinking is dominated by the experiential system (ef. Simon et al, 1997). Several studies have been conducted in which the modes have been pitted against each other, yielding support for the theory (e.g., Denes-Raj & Epstein, 1994;Epstein et al, 1992).…”
Section: Rational and Experiential Systemsmentioning
confidence: 99%